Description of Social Support for Postpartum Mothers in The Working Area of The Dukuh Kupang Community Health Center of Surabaya City - Sholikhah, Faridatus; Afridah, Wiwik (Rifa'Institute, 2022)
Introduction: Postpartum is a physical and psychological adjustment to the birth process. Social support is one of the factors that can influence the occurrence of psychological disorders. The role of social support provided can improve mental health and psychological well-being. Objective: The purpose of this study describes the picture of social support for postpartum mothers in the work area of the Dukuh Kupang Health Center, Surabaya City. Method: In this study, the research used quantitative descriptive methods. Data retrieved in January – June 2022. The data used is primary data using a questionnaire. The population in this study was all postpartum mothers with a total of 36 postpartum mothers. The sampling technique uses total sampling. Data analysis uses univariate single data analysis. Result and Discussion: The results of this study showed that postpartum mothers in the work area of puskesmas Dukuh Kupang Kota Surabaya almost all (88.9%) had good emotional support, almost all (97.2%) had good award support, almost all (91.7%) had good instrumental support, almost all (94.4%) had good information support. Conclusion: The conclusion of the results of this study is that the identification of postpartum mothers in the work area of the Dukuh Kupang Health Center, Surabaya City, almost entirely received good social support. Advice for puskesmas to provide preventive efforts to postpartum mothers, for the community to increase emotional support in postpartum mothers again.